Effectiveness of Licensing Services at Public Service Mall of Semarang Regency - Jatu Cynthia Restu; Tri Yuniningsih (Universitas Sebelas Maret, 2025)
Public service is one of the government's important functions in realizing good governance. One form of public service delivery in Indonesia is the Public Service Mall, which is expected to provide convenience, speed, reach, comfort, and security of service to the public. However, in Semarang Regency, the achievements of the Investment Coordinating Board (BKPM) and the Ombudsman have not been fully reflected in the quality of service perceived by the public. The Public Satisfaction Index for Licensing Services from 2021 to 2023 experienced instability, with a value of 93.73 in 2021 to 92.75 in 2022, and only increasing by 0.25 to 93 in 2023. Furthermore, investment growth also showed inconsistent fluctuations. This study aims to analyze the effectiveness of licensing services at the Semarang Regency Public Service Mall (MPP) using Richard M. Steers' (1985) effectiveness theory with three models: goal optimization, system perspective, and behavioral pressure. A qualitative approach within descriptive research was employed while utilizing both primary and secondary data sources. This study’s findings revealed that Semarang Regency MPP’s licensing services are not yet fully effective. Several barriers remain including, a lack of alignment between organizational goals and outcomes, poor inter-agency collaboration, limited HR capacity, weak digital technology utilization and innovation, and a lack of adaptive responsiveness to external demands. Therefore, this study recommends strategic steps to improve the effectiveness and quality of licensing services at the Semarang Regency Public Service Mall by strengthening human resource capacity, optimizing inter-agency coordination, maximizing digital system utilization, developing proactive service innovations that are user-oriented to realize professional, integrated, innovative, user-satisfaction-oriented public services, and supporting the creation of good governance and a conducive investment climate.